A bodipy based fluorescent probe for evaluating and identifying cancer, normal and apoptotic C6 cells on the basis of changes in intracellular viscosity. Issue 11 (25th February 2016) - Gupta, Neha; Reja, Shahi Imam; Bhalla, Vandana; Gupta, Muskan; Kaur, Gurcharan; Kumar, Manoj
Abstract : A bodipy based probe1 has been explored for the identification of diseased cell population out of normal cells on the basis of changes in intracellular viscosity. Abstract : The applications of a bodipy based probe1 for the identification of diseased cell population out of normal cells on the basis of changes in intracellular viscosity have been explored. Probe1 works on the principle of restriction of rotation in viscous medium and the molecular rotor nature of probe1 is supported by low temperature 1 H NMR and variable dihedral angle DFT and TD-DFT studies. More importantly, probe1 is the first probe which shows its practical application in monitoring micro-viscosity changes in a cell based model system of undifferentiated, differentiated and apoptotic C6 glial cells. Further, probe1 can effectively monitor the apoptosis pathway by showing an increase in fluorescence intensity from cancerous cells to apoptotic cells via real time live-cell video imaging. Moreover, the viscosity changes in living cells were proved by fluorescence lifetime imaging (FLIM) studies, flow cytometry using Annexin-V and Bcl-xl expression by immunocytofluorescence (ICC) and western blot analysis.